Consecutive three-component synthesis of film luminescent indolone merocyanines with L-amino acid ester donors - Muschelknautz, Christian; Mayer, B.; Rominger, Frank; Müller, Thomas J. J. (Chemistry of heterocyclic compounds, 2013)
Prop-2-enylidene indolones substituted with L-amino acid esters are obtained in good to excellent yields in a consecutive three-component cyclocarbopalladation, Sonogashira coupling, and Michael addition sequence. While primary L-amino acid esters furnish a mixture of E,E- and E,Z-configurated diastereomers, L-proline methyl ester selectively and exclusively furnishes the E,E-isomer. As already discovered for other 3-aminoprop-2-enylidene indolones, the drop-casted films of all representatives display pronounced aggregation-induced orange-red fluorescence with large Stokes shifts, while all chromophores are nonemissive in solution.